U-Pb Age Constraints on the Jurassic Succession and Paleoflora of Mount Flora, Antarctic Peninsula - Scasso, Roberto Adrian; Ramezani, Jahandar; Escapa, Ignacio Hernán; Elgorriaga, Andrés; Capelli, Ignacio Andrés (International Journal of Earth Sciences)
The spectacular fossil plant assemblage preserved in the non-marine Mount Flora Formation of the northern Antarctic Peninsula represents the diverse Jurassic flora that once covered the Gondwanan continents at high paleolatitudes. The depositional facies of the formation plays a key role in the tectonic interpretations and basin evolution models that attempt to reconcile large igneous province magmatism, continental break up, and magmatic arc development throughout the Jurassic and Cretaceous. Limited U–Pb in situ geochronology reported from the Mount Flora Formation and adjacent units lack the necessary resolution to overcome ambiguous correlations and biostratigraphic discrepancies. We present two high-precision U–Pb zircon ages (CA-ID-TIMS method) from a distinct tuffaceous interval of the Mount Flora Formation at Hope Bay, which document a terminal Middle Jurassic age (Callovian Stage) for the formation and its paleoflora. In excess of 1400 new collected fossil plant specimens exhibit a highly diverse Jurassic plant association that dominated the Antarctic Peninsula nearly 17 million years after its disappearance from northern Patagonia. This suggests similar paleoecological conditions were established diachronously throughout basins of southern Gondwana, possibly facilitating floral migrations in response to local climate change. The depositional facies of the Mount Flora Formation, its age proximity to the marine Nordenskjöld Formation in the Antarctic Larsen Basin and its coincidence with a regional unconformity in the northern Patagonia point out to a complex interplay among magmatic arc development, tectonic extension and continental break up that dominated the geologic and paleoenvironmental evolution of southern Gondwana near the end of the Middle Jurassic. Fil: Scasso, Roberto Adrian. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires. Universidad de Buenos ...